A relação entre o grau de internacionalização das empresas e as remunerações salariais - Marques, Ana Rita de Freitas (2021)
This dissertation aims to understand the relationship between the internationalization of companies through commercial channels - exports and imports of goods and services - and wage remuneration, investigating whether workers who work in internationalized Portuguese companies receive a wage premium, that is, if their salary average is higher than for those who work in companies that do not operate in the foreign market. For this purpose, a set of SABI data at company level in Portugal is used to analyze the wage premium associated with export and/or import activities. The sample covers 18318 Portuguese companies with at least 10 workers, from all sectors of economic activity, in the period 2010-2019. Thus, through an econometric study, it was investigated the hypothesis that wages paid by Portuguese companies are influenced by their international activity, which was validated by the results obtained. The results obtained indicate that exporting companies pay a wage premium of approximately 20%, once the influence of relevant control variables is considered, including the size of the companies, their capital intensity and their section of the activity. However, when additional consideration is given to the possibility of them also having an import activity, the salary premium for exporters increases to 15% and that for importers is 10%. Finally, when analyzing the wage premium of companies that only export, only import or export and import simultaneously, the wage premium of companies that only export is 13% and that of companies that export and import simultaneously is 26%.